A booming trade?: how collection of war residues affects livelihoods and forest in Vietnam - Boissiere, M.; Sheil, Douglas; Basuki, I. (2011)
We investigated how demand for war derived scrap metal influenced livelihoods, forest use and environmental outcomes near the biodiverse Annamite Mountains in Central Vietnam. We focused on one community, Khe Tran, and interviewed local villagers, active collectors from other communes, traders and officials. We also visited the forest. Collection is illegal during the dry season due to concerns about fires. Despite the threat of unexploded ordnance, villagers did not judge metal collection especially dangerous. Though metal is declining, scrap collection remained the principle reason people entered the forest. Though many Khe Tran villagers had past experiences as metal collectors most now favoured cultivation and plantation management. In contrast many collectors from elsewhere lacked such options. Collectors often sought other products when looking for metal, thereby facilitating trade in these forest products (e.g. bamboo and rattan). Alternative livelihood options are required for those reliant on this finite and declining resource.